2014
DOI: 10.3109/13816810.2014.881505
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Dystrophy with Intraretinal Cystoid Spaces Associated with Mutations in the Crumbs Homologue (CRB1) Gene

Abstract: CRB1 mutations may be associated with intraretinal cystoid spaces. The use of carbonic anhydrase inhibitors can result in improved visual acuity in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Further studies on CAI treatment showed a rebound effect in RS1 in a small subset of patients only 14. A different response to treatment with oral CAI might be possible for various genotypes in RS1 (including the side effects), as previously reported 1518…”
Section: Introductionsupporting
confidence: 51%
“…Further studies on CAI treatment showed a rebound effect in RS1 in a small subset of patients only 14. A different response to treatment with oral CAI might be possible for various genotypes in RS1 (including the side effects), as previously reported 1518…”
Section: Introductionsupporting
confidence: 51%
“…The most prominent are hypermetropic refractive error, nummular pigmentation, intraretinal cystoid spaces, retinal thickening with loss/reduced retinal lamination, and occasionally there may also be sparing of para-arteriolar RPE [22,23]; all of these features were observed in proband 3, and lead us to screen CRB1 by Sanger sequencing as an initial approach. In proband 2, with advanced disease, the aforementioned clinical examination features were not readily recognizable and she was initially referred to a geneticist with a diagnosis of autosomal recessive RP, which resulted in genetic screening using an AR RP microarray.…”
Section: Discussionmentioning
confidence: 99%
“…The genes most frequently linked with RP include RHO , USH2A , RPGR , CRB1 , GUCY2D , and RPGPIP1 [11]. Previous studies reported CRB1 mutations in ARRP in diverse populations [2, 11, 12, 14]. This study identified a pair of novel compound mutations in CRB1 in a Chinese pedigree with ARRP.…”
Section: Discussionmentioning
confidence: 80%